Environmental background radiation for some drug samples used by children in Iraq - Mohammed Torki Wedyan; Saeed Jassim Ali; Abid Abojassim Ali; Abdul Hadi Mohsen Ahmed; Hayder Rand A. (E3S Web of Conferences)
This study measures at the radiation levels in antibiotic samples commonly used for children in Iraq. This study used the FS-600 dosimeter. Antibiotic samples’ radiation dose (D) and yearly effective dose (AED) were tested. The dose rate (μSv/h) ranged from 0.11 μSv/h to 0.19 μSv/h, with an average of 0.127, give or take 0.029 μSv/h. The AED values varied between 0.73 mSv/y and 1.67 mSv/y, with an average of 1.116 mSv/y plus or minus 0.250 mSv/y. The radiation levels and yearly exposure from all drug samples used for children are safe and below the limits set by UNSCEAR 2008 and NCRP 2009. So, the tested samples are considered safe in terms of radiation level and do not pose a significant risk.